Dampak Akta Kelahiran bagi Kehidupan Ekonomi Keluarga: Studi Kasus di Kota Administrasi Jakarta Pusat - Andi Rahma (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The economic impact of birth certificates on family life in Central Jakarta demonstrates that a birth certificate constitutes a child’s civil right, determining legal identity recognition and influencing the fulfillment of civil rights. This study analyzes the impact of birth certificate ownership on family economic conditions in Central Jakarta using an empirical juridical method with a socio-legal approach based on interviews and regulatory review. Findings show that despite adequate public services, some children remain unregistered due to economic constraints and limited procedural understanding, restricting access to education, social assistance and public services, thereby affecting family economic resilience.